2010
DOI: 10.1183/09031936.00063510
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of etanercept in moderate-to-severe asthma: a randomised, controlled trial

Abstract: Increased tumour necrosis factor-a levels have been observed in bronchial biopsies and induced sputum from subjects with severe asthma. We investigated etanercept (ETN) as a therapeutic option for treating moderate-to-severe persistent asthma.In this 12-week, randomised, double-blind, placebo-controlled, phase 2 trial, subjects (n5132) with moderate-to-severe persistent asthma received subcutaneous injections of 25 mg ETN or placebo twice weekly, and were evaluated at baseline, and at weeks 2, 4, 8 and 12. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(87 citation statements)
references
References 41 publications
(61 reference statements)
3
80
2
2
Order By: Relevance
“…The resulting cells were incubated with biotinylated antibodies against the lineage markers CD31, CD34, and CD45, and an AutoMACS column was used to deplete nonepithelial cells. AECs were then subjected to flow cytometry-based sorting as (21,22), but others not (23,52). It seems likely that this is because blockade of TNF is efficacious in only a subgroup of patients, which is consistent with our current finding that TNF is required in some, but not all, models of asthma.…”
Section: Discussionsupporting
confidence: 76%
“…The resulting cells were incubated with biotinylated antibodies against the lineage markers CD31, CD34, and CD45, and an AutoMACS column was used to deplete nonepithelial cells. AECs were then subjected to flow cytometry-based sorting as (21,22), but others not (23,52). It seems likely that this is because blockade of TNF is efficacious in only a subgroup of patients, which is consistent with our current finding that TNF is required in some, but not all, models of asthma.…”
Section: Discussionsupporting
confidence: 76%
“…Neutralizing TNFα restores corticosteroid sensitivity in a mouse model of neutrophilic airway inflammation [Dejager et al 2015]. Several small clinical studies in severe asthma of the soluble TNF-α receptor blocker etanercept reported beneficial effects on clinical outcomes [Howarth et al 2005;Berry et al 2006], whereas larger studies with etanercept [Holgate et al 2011] and the TNF-α receptor blocker golimumab [Wenzel et al 2009] did not confirm a consistent beneficial clinical effect. When combined with concerns over increased risk of severe infections and malignancies with TNF-α receptor blocker treatment [Wenzel et al 2009] it is unlikely that this target will be developed further for the treatment of asthma.…”
Section: Il-17 Blockersmentioning
confidence: 99%
“…However, recent studies targeting tumor necrosis factor-α in human subjects have failed to show improved clinical end points (61).…”
Section: (Failure Of) Targeted Therapiesmentioning
confidence: 99%